Comparative Susceptibility of Haemophilus Species to Cefaclor, Cefamandole, and Five Other Cephalosporins and Ampicillin, Chloramphenicol, and Tetracycline - Watanakunakorn, Chatrchai (1979)
The minimal inhibitory concentration of cefaclor, cephalexin, cephradine, cefamandole, cephalothin, cephapirin, cefazolin, ampicillin, chloramphenicol, and tetracycline for inhibition of 198 freshly isolated clinical strains of Haemophilus species (23 H. influenzae type b, 157 H. influenzae non-type b, 14 H. parainfluenzae, and 4 H. aphrophilus) was determined simultaneously by a slightly modified WHO-ICS agar dilution method. Nine strains were resistant to ampicillin. There was no correlation between ampicillin resistance and minimal inhibitory concentration of other antibiotics. All strains were susceptible to chloramphenicol, and all except five were susceptible to tetracycline. Cefaclor was the most active oral cephalosporin, and cefamandole was the most active parenteral cephalosporin. Among the seven cephalosporins tested, cefamandole was the most effective compound. All but two strains were inhibited by cefamandole at 2 μg or less per ml.